Representaciones Sociales Sobre El Consumo De Bebidas Alcohólicas Presentes en los Estudiantes de La Facultad de Psicología de La Universidad Antonio Nariño – Jornada Nocturna/Sede Sur (2016)
Alcohol is considered a psychoactive substance, which produces dependence, when consumes excessively, it is among the first five risk factors for the disease, disability and death worldwide, as well as affecting behavior and health mental health, the harmful use of alcoholic beverages has the greatest impact among young people aged 18 to 24 years, the city of Bogotá ranks 20th nationally, there are 2,219,170 consumers, which is equivalent to 39.49% of the capital's total population, which is equivalent to a 9.99% of the population, on the other hand, the Rafael Uribe Uribe town is the eighth most largest city, has 375,625 inhabitants, which would be 6.2% of the total population capital and 60% of its inhabitants are in the age range of 15 to 55 years.